Carbonic anhydrase seven bundles filamentous actin and regulates dendritic spine morphology and density. (15th March 2021) - Bertling, Enni; Blaesse, Peter; Seja, Patricia; Kremneva, Elena; Gateva, Gergana; Virtanen, Mari A; Summanen, Milla; Spoljaric, Inkeri; Uvarov, Pavel; Blaesse, Michael; Paavilainen, Ville O; Vutskits, Laszlo; et al.
Abstract: Intracellular pH is a potent modulator of neuronal functions. By catalyzing (de)hydration of CO2, intracellular carbonic anhydrase (CAi ) isoforms CA2 and CA7 contribute to neuronal pH buffering and dynamics. The presence of two highly active isoforms in neurons suggests that they may serve isozyme‐specific functions unrelated to CO2 ‐(de)hydration. Here, we show that CA7, unlike CA2, binds to filamentous actin, and its overexpression induces formation of thick actin bundles and membrane protrusions in fibroblasts. In CA7‐overexpressing neurons, CA7 is enriched in dendritic spines, which leads to aberrant spine morphology. We identified amino acids unique to CA7 that are required for direct actin interactions, promoting actin filament bundling and spine targeting. Disruption of CA7 expression in neocortical neurons leads to higher spine density due to increased proportion of small spines. Thus, our work demonstrates highly distinct subcellular expression patterns of CA7 and CA2, and a novel, structural role of CA7. Synopsis: Carbonic anhydrase CA7 is a pH‐regulatory molecule that is expressed in pyramidal neurons at the time of onset of dendritic spinogenesis. This study shows that CA7, but not CA2, binds and bundles actin filaments and has a morphogenetic role in cells. CA7 binds and bundles actin filaments in vitro . CA7‐overexpression induces actin filament bundling and leads to aberrant spine morphology in neurons. Knockout of CA7 leads to higher spine density and smaller spines in vivo . Abstract : Carbonic anhydrase CA7 is a pH‐regulatory molecule that is expressed in pyramidal neurons at the time of onset of dendritic spinogenesis. This study shows that CA7, but not CA2, binds and bundles actin filaments and has a morphogenetic role in cells.